Significant Association between Serum Interleukin-6 and Helicobacter pylori Antibody Levels among H. pylori-Positive Japanese Adults - Hiroko Nakagawa; Takashi Tamura; Yoko Mitsuda; Yasuyuki Goto; Yoshikazu Kamiya; Takaaki Kondo; Kenji Wakai; Nobuyuki Hamajima (Mediators of Inflammation)
Background. Interleukin-6 (IL-6) is a multifunctional cytokine produced by many types of cells. Inflammation plays a key role in the pathogenesis of atherosclerosis that is an underlying cause of coronary heart disease (CHD). Since the 1990s, some studies have shown an association between H. pylori infection and CHD, which may be mediated by inflammation. Therefore, this study aimed to evaluate the association between serum anti-H. pylori IgG levels and serum IL-6 levels in H. pylori-infected adults. Methods. We enrolled 158 subjects who visited a clinic located in an urban area to be tested for H. pylori infection, using the 13C-urea breath test, and who were found to be infected and subsequently received eradication. Results. The geometric mean serum IL-6 level was 1.78 pg/mL for men, 1.57 pg/mL for women, and 1.64 pg/mL overall. Logarithms of serum IL-6 levels were positively correlated with logarithms of serum H. pylori IgG levels (r=0.24, P=0.002). In multiple linear regression analysis adjusting for sex and age, the serum IL-6 level was still significantly associated with the IgG level in all subjects (β=0.18, P=0.012). Conclusion. Higher H. pylori IgG levels were significantly associated with higher serum IL-6 levels among H. pylori-infected individuals.